New Schemes for Investment in of Small and Medium-Sized Enterprises of China: Role of Access to Finance, Innovation, and Sustainability - Tang, Xuelian (Frontiers in Psychology, 2022)
Firm innovation relies heavily on financing, which is why it is a hot topic in the fields of finance and innovation management. Organizations can make strategic investments in production factors to develop competitive advantages because they have access to financial resources. This study investigated how financial literacy, innovativeness, and environmental sustainability influence the sustainability of small and medium-sized enterprises (SMEs). This was set as the primary objective in order to better understand the nature of the impact of financial literacy and innovation on the sustainability of SME firms. To test the hypotheses, structural equation modeling (SEM) was applied using data collected from 300 small businesses firms in China. The results revealed that financial literacy and innovativeness significantly influence small firms’ sustainability. Additionally, social inclusion significantly affects small firms’ sustainability, and sequentially has a significant effect on their performance. Research findings suggested that small businesses incorporate sustainability models into their operations and enhance financial knowledge in order to maintain sustainability.